Telemedicine for Diabetes Mellitus Patients in the Middle of Pandemic Covid-19 - Ni Made Candra Citra Sari; Etty Rekawati (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
The determination of the Covid-19 as pandemic globally has led to changes in all existing sectors, one of them is the health sector. Health services for diabetes patients have also changed, in which patients with diabetes are limited in their visits to health services, to reduce the risk of people with diabetes being exposed to Covid-19. In return, health services are provided virtually. The research method used was literature studies with search sources through online databases such as SagePub, Sciencedirect, Springer dan GoogleScholar. From the literature search, it was obtained 7 research articles which were published in the range of 2020-2021. Based on the seven (7) reviewed articles, it was obtained that online health services health services have been proven to be effective in improving glycemic control for people with diabetes. This virtual health service is highly expected by patients with diabetes mellitus to be used as an alternative in health services even though the Covid-19 pandemic will have ended.